2012
DOI: 10.1371/journal.pone.0035244
|View full text |Cite
|
Sign up to set email alerts
|

Directed Induction of Functional Motor Neuron-Like Cells from Genetically Engineered Human Mesenchymal Stem Cells

Abstract: Cell replacement using stem cells is a promising therapeutic approach to treat degenerative motor neuron (MN) disorders, such as amyotrophic lateral sclerosis and spinal cord injury. Human bone marrow-derived mesenchymal stem cells (hMSCs) are a desirable cell source for autologous cell replacement therapy to treat nervous system injury due to their plasticity, low immunogenicity, and a lower risk of tumor formation than embryonic stem cells. However, hMSCs are inefficient with regards to differentiating into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…It also induces the expression of a motor neuron marker, called Islet-1 in postmitotic precursors [35]. Treatment of MSCs with RA and Shh induces the upregulation of Islet-1 and ChAT in genetically engineered human mesenchymal stem cells which induced to express Hb-9 transcription factor [36].…”
Section: Discussionmentioning
confidence: 99%
“…It also induces the expression of a motor neuron marker, called Islet-1 in postmitotic precursors [35]. Treatment of MSCs with RA and Shh induces the upregulation of Islet-1 and ChAT in genetically engineered human mesenchymal stem cells which induced to express Hb-9 transcription factor [36].…”
Section: Discussionmentioning
confidence: 99%
“…According to his method, human MSCs were exposed to histone deacetylases inhibitor (Trichostatin), DNA methyltransferase inhibitor (RG-108), biologically active form of cAMP, and phosphodiesterases inhibitor (Rolipram) in a medium consisting of NeuroCult/N2 supplemented with bFGF for two weeks before transplantation. Park et al, reported a new method to generate functional motor neuron (MN)-like cells from genetically engineered human MSCs [141]. They transduced motor neuron-associated transcription factor gene expression into the human MSC, then they treated the genetically engineered MSCs expressing Olig2 and Hb9 with optimal MN induction medium.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…(36) Altered iron homeostasis also has been described in Huntington disease (HD), invitro studies results supported this data. (37) Amylotropic lateral sclerosis (ALS) ALS IS a devastating neurological disorder which has a vascular component. Invitro studies proved that molecules like vascular endothelial growth factor (VEGF) have a therapeutic, diagnostic and prognostic potential in ALS.…”
Section: In-vitro Trials Involving Mechanisms Of Stem Cell-mentioning
confidence: 99%